Generation and differentiation of induced pluripotent stem cells reveal ankylosing spondylitis risk gene expression in bone progenitors. Issue 1 (January 2017) - Layh-Schmitt, Gerlinde; Lu, Shajia; Navid, Fatemeh; Brooks, Stephen; Lazowick, Emily; Davis, Kathryn; Montagna, Cristina; Gadina, Massimo; Colbert, Robert
Abstract Axial spondyloarthritis (axSpA), which encompasses ankylosing spondylitis, is a complex genetic disease. Aberrant bone formation is a key feature of pathogenesis that can lead to ankylosis of the spine. Our objective is to determine, whether genes whose variants confer susceptibility to AS are expressed in bone progenitors like mesenchymal stem cells (MSCs). Since MSCs from bone marrow is difficult to obtain, we first examined, whether MSCs can be derived from induced pluripotent stem cells (iPSCs). Dermal fibroblasts of two axSpA patients and one healthy control were reprogrammed into iPSCs using a Sendai virus vector encoding pluripotency genes. Pluripotency of iPSCs was examined by embryoid body formation and by testing for stem cell specific gene and protein expression using RT-PCR and immuno fluorescence. iPSCs were differentiated into MSCs by a TGFß inhibitor. MSCs were characterized by flow cytometry using lineage specific antibodies and by their capacity to develop into chondrocytes, adipocytes, and osteoblasts in lineage-specific medium. RNA-seq was applied to determine genome-wide gene expression patterns in MSCs, iPSCs, and blood. We show for the first time, that expression levels of several AS susceptibility genes (EDIL3, ANO6, HAPLN1, ANTXR2) involved in bone formation are significantly elevated in MSCs (2–15-fold;p  ≤ 0.05) compared to blood or iPSCs and demonstrate that iPSC-derived MSCs can be differentiated into osteoblasts, chondrocytes, and adipocytes. We conclude, MSCs generated from patient fibroblast-derived iPSC lines are useful tools for studying functional genomics of risk genes associated with bone formation in AS pathogenesis.